A Global Positioning System study for a sub elite Australian Rules Football team: A case study of the Glenelg Football Club. - Raidis, D. (Journal of Australian Strength and Conditioning, 2013)
The monitoring of movement patterns using Global Positioning system (GPS) has become prevalent in the elite football sides that compete in the Australian Football League (AFL). However, studies in GPS in sub elite football teams remain limited. This case study presents a GPS study at the Glenelg Football Club, who compete in the sub elite South Australian National Football League, aimed at improving player performance. Match and training day data were monitored in the 2011 season (n = 84 match files, n = 96 training files). Players were fitted with 5 Hz SPI Pro GPS units prior to matches and main training sessions. Data was downloaded post matches and trainings into the following: various speed zones, total distance, maximum speed, number of sprints. Three Key Performance Indicators were selected and calculated to form a basis of all analysis. They were: distance per minute, effort running and intensity. The indicators also assisted to evaluate the efficacy of training drills during the in-season. The results of the sub elite footballers were then compared to elite listed Australian Football League team mates and indicated that the latter run further per minute, have higher intensity and effort running. Hence, one of the practical implications of this study is to help coaches use GPS more effectively in the preparation of their athletes. It is also of benefit to Strength and Conditioning staff whom require assistance in setting up their own entry level GPS study.